Robot-Assisted Laparoscopic Radical Cystectomy and Modified Y-Shaped Ileal Orthotopic Neobladder Reconstruction - Mao, Weipu; Chen, Shuqiu; Zhang, Lijie; Li, Tao; Sun, Si; Xu, Bin; Zhu, Weidong; Zhang, Guangyuan; Zhang, Lei; Wu, Jianping; Chen, Ming (Frontiers in Surgery, 2022)
Background Orthotopic neobladder reconstruction has become the preferred method of urinary diversion after radical cystectomy in major medical centers. We performed modified Y-shaped ileal orthotopic neobladder reconstruction and presented the functional results and postoperative complications of the modified surgery. Methods We included 21 patients with bladder cancer who underwent radical cystectomy at our center between February 2019 and December 2019. All patients underwent robotic-assisted laparoscopic radical cystectomy and lymph node dissection plus modified Y-shaped ileal orthotopic neobladder reconstruction. We collected the demographic and pathological history of the patients, and perioperative and postoperative functional outcomes and postoperative complications were recorded. Results All surgeries were successful and no serious postoperative complications occurred. The mean operative time was 321.43 ± 54.75 min, including 101.67 ± 10.88 min required for neobladder reconstruction. Liquid intake was encouraged about 5 days after surgery, stent and catheter were removed after 13.52 ± 3.28 days, and the patients were discharged 1–2 days after removing the catheter. No ureteral anastomotic and neobladder urethral anastomotic strictures occurred. The volume of the neobladder at 1-year post-surgery was 195.24 ± 16.07 mL and the maximum urinary flow rate was 20.64 ± 2.22 mL/s. Conclusion We describe the robotic-assisted modified Y-shaped ileal orthotopic neobladder reconstruction performed at our center, which requires a simple suture and short neobladder construction time, minimizes the occurrence of anastomotic stenosis, facilitates smooth patient emptying, and is clinically scalable and applicable.